That's not funny : how the right makes comedy work for them - Sienkiewicz, Matt; Marx, Nick (University of California Press, 2022)
"Why do conservatives hate comedy? Why is there no right-wing Jon Stewart?" These sorts of questions launch a million tweets, a thousand op-eds, and more than a few scholarly analyses. That's Not Funny argues that it is both an intellectual and politically strategic mistake to assume that comedy has a liberal bias. In this book, authors Matt Sienkiewicz and Nick Marx take readers--particularly self-described liberals--on a tour of contemporary conservative comedy and the "right-wing comedy complex." In That's Not Funny, "complex" takes on an important double meaning. On the one hand, liberals have developed a social-psychological complex-it feels difficult, even dangerous, to acknowledge that their political opposition can produce comedy. At the same time, the right has been slowly building up a comedy-industrial complex, utilizing the humorous, irony-laden media strategies of liberals such as Jon Stewart, Samantha Bee, and John Oliver to garner audiences and supporters. Right-wing comedy has been hiding in plain sight, finding its way into mainstream conservative media through figures ranging from Fox News's Greg Gutfeld to libertarian podcasters like Joe Rogan. That's Not Funny guides readers through media history, text, and technique, and interviews with and observations of conservative comedians in action. You will find many of these comedians utterly appalling, some surprisingly funny, and others just plain weird. They are all, however, culturally and politically relevant-the American right is attempting to seize spaces of comedy and irony previously held firmly by the left. You might not like this brand of humor, but you can't ignore it --